2012
DOI: 10.5551/jat.9035
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin Low-Density-Lipoprotein Serves as a Marker of Smoking-Specific Oxidative Stress

Abstract: Aim: While smoking cessation (SC) leads to a reduction of cardiovascular events, atherogenic biomarkers specifically connected with cigarette smoking and SC are unknown. Circulating levels of oxidatively modified low-density-lipoprotein (LDL) are associated with a high risk of cardiovascular diseases. Recently, two novel, oxidatively modified LDL markers, serum amyloid A-LDL (SAA-LDL) and 1-antitrypsin-LDL (AT-LDL), were identified; however, the significance of SAA-LDL and AT-LDL as cardiovascular risk markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Although the mechanisms are not still clear, oxidative stress may play an important role between HSP 27 and cigarette smoking [22,23]. Further, the present study indicated a clear dose-response relationship between HSP 27 and smoking status, in which HSP 27 might be increased as a marker of smoking-specific oxidative stress [24]. Although former smokers were included in the no smoker group in this study, former smokers showed an almost normal range of HSP 27 levels.…”
Section: Plasma Hsp 27 Levels and Smoking Habitsmentioning
confidence: 82%
“…Although the mechanisms are not still clear, oxidative stress may play an important role between HSP 27 and cigarette smoking [22,23]. Further, the present study indicated a clear dose-response relationship between HSP 27 and smoking status, in which HSP 27 might be increased as a marker of smoking-specific oxidative stress [24]. Although former smokers were included in the no smoker group in this study, former smokers showed an almost normal range of HSP 27 levels.…”
Section: Plasma Hsp 27 Levels and Smoking Habitsmentioning
confidence: 82%
“…We employed the Stat View 5.0 software program (for Windows) for the data analysis, which was performed as previously described 17) . Briefly, the correlations between the serum sLOX-1 levels and other parameters were examined according to Pearson's correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…BMI, body mass index; SBP, systolic blood pressure; DBP, diastolic blood pressure; HbA 1c, hemoglobin A 1c; HDL-C, highdensity lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; hsCRP, high-sensitivity C-reactive protein; CO, carbon monoxide; SDS, Self-rating Depression Scale; FTND, Fagerstrom Test for Nicotine Dependence; sLOX-1, soluble LOX-1 determinants of the serum alpha1-antitrypsin-LDL (AT-LDL) level 17) . However, the AT-LDL level exhibits no correlation with the number of cigarettes smoked per day, the expired air CO concentration or the hsCRP level.…”
Section: Correlations Between the Serum Slox-1 Levels And Clinical Pamentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of AT-LDL levels in smokers and nonsmokers indicated that AT-LDL levels are significantly elevated in smokers 29. AT-LDL is an oxidatively modified LDL, and AT-LDL levels quickly drop as a result of smoking cessation, which suggests that AT-LDL promotes atherosclerosis and is closely related to smoking.…”
Section: Discussionmentioning
confidence: 99%